2002
DOI: 10.1108/13522750210432995
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of the influencing factors on the decision process for acquiring ERP software

Abstract: This paper focuses on the influences and characteristics of the enterprise resource planning (ERP) acquisition process (ERPAP) that were found during a multiple-case study of four organizations that had acquired ERP solutions. From organizational buying behaviour (OBB), Webster and Wind's (Prentice-Hall, Englewood Cliffs, NJ, 1972) served as the basis for categorizing the influences that surfaced during the study. While Webster and Wind's model presents a broad scope of variables that might affect organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Focused stage Bernroider and Koch, 2001;Stefanou, 2001;Verville, 2002a;Gefen, 2002;Verville, 2002b;Alvarez and Urla, 2002;Bryson and Sullivan, 2003;Arinze and Anandarajan, 2003;Verville, 2003a;2003b;Wei and Wang, 2004;Bendoly and Jacobs, 2004;Luo and Strong, 2004;Wei et al, 2005a;Baki and Cakar, 2005;Verville et al, 2005 Cultural issues Soh et al, 2000;Krumbholz et al, 2000;Adam and O'Doherty, 2000;Krumbholz and Maiden, 2001;Sheu et al, 2004;Baki et al, 2004;Boersma and Kingma, 2005a;Xue et al, 2005;Wang et al, 2005;Zhang et al, 2005;Tsai et al, 2005;Baki and Cakar, 2005;Bendoly et al, 2006;Jones et al, 2006;Yusuf et al, 2006 Table 3 Themes and references (continued)…”
Section: Themes Referencesmentioning
confidence: 99%
“…Focused stage Bernroider and Koch, 2001;Stefanou, 2001;Verville, 2002a;Gefen, 2002;Verville, 2002b;Alvarez and Urla, 2002;Bryson and Sullivan, 2003;Arinze and Anandarajan, 2003;Verville, 2003a;2003b;Wei and Wang, 2004;Bendoly and Jacobs, 2004;Luo and Strong, 2004;Wei et al, 2005a;Baki and Cakar, 2005;Verville et al, 2005 Cultural issues Soh et al, 2000;Krumbholz et al, 2000;Adam and O'Doherty, 2000;Krumbholz and Maiden, 2001;Sheu et al, 2004;Baki et al, 2004;Boersma and Kingma, 2005a;Xue et al, 2005;Wang et al, 2005;Zhang et al, 2005;Tsai et al, 2005;Baki and Cakar, 2005;Bendoly et al, 2006;Jones et al, 2006;Yusuf et al, 2006 Table 3 Themes and references (continued)…”
Section: Themes Referencesmentioning
confidence: 99%
“…As mentioned in the literature review, some research in regards to ERP selection has been done [18], [19], [20], [21], [35], mainly with the focus on larger enterprises [2], [22], [36]. But the specific requirements that arise when applying an IT operational viewpoint have not been taken into consideration.…”
Section: Erp Selection Criteriamentioning
confidence: 99%
“…Most of the research done regarding the ERP selection process is focused towards larger enterprises [2], [22], [36]. Small and medium size enterprises (SME) are addressed by Bernroider and Koch [23], Lin and Ford [37] and Wei et al [24].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Francoise (2009) stressed for more user involvement throughout the IS implementation project, since end-users knowledge can be used in areas where the IS team lacks the expertise. Verville et al (2006) showed that endusers involvement in acquisition phase of IS system results in end-users desire for technology purchase. The end-users desire for technology acquisition according to Verville et al (2006) resulted in end-users open acceptance of the IS application following the implementation.…”
Section: N=200mentioning
confidence: 99%
“…Verville et al (2006) showed that endusers involvement in acquisition phase of IS system results in end-users desire for technology purchase. The end-users desire for technology acquisition according to Verville et al (2006) resulted in end-users open acceptance of the IS application following the implementation. It was noted from the analysis that end user training had a significant influence on strategic information systems implementation.…”
Section: N=200mentioning
confidence: 99%